2011
DOI: 10.4097/kjae.2011.60.6.444
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of non-cardiac surgery with adult onset type of cor triatriatum sinister -A case report-

Abstract: A 45-year-old woman with cor triatriatum sinister was admitted for laparoscopic resection of an ovarian tumor. Her medical history was benign with the exception of a single episode of syncope one year ago. A 1.5-cm membrane fenestration was found on echocardiography, but there were no other cardiac structural anomalies. General anesthesia was established with etomidate, sevoflurane, and remifentanil; no notable events occurred during the anesthesia. As cor triatriatum shows a clinical picture of mitral stenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…We identified only six publications that describe patients with uncorrected CT undergoing anesthesia. [11][12][13][14][15][16] Two reports described two adult patients with asymptomatic CTS who had uneventful perioperative course. [14,15] In four isolated reports patients had CTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified only six publications that describe patients with uncorrected CT undergoing anesthesia. [11][12][13][14][15][16] Two reports described two adult patients with asymptomatic CTS who had uneventful perioperative course. [14,15] In four isolated reports patients had CTD.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Two reports described two adult patients with asymptomatic CTS who had uneventful perioperative course. [14,15] In four isolated reports patients had CTD. [11][12][13]16] One patient, a 67-year-old man with non-obstructive CTD, underwent hydrocelectomy uneventfully.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cold, stress, dehydration, infections, inflammatory cascades, hypoxia, and acidosis are some predisposing factors for sickling. These conditions are pretty common in cardiac surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports indicate that patients with CorT require careful management because of myocardial substance damage or hemodynamic problems in non-treated CorT. For example, Lee et al [11] reported that CorT presents a clinical picture of mitral stenosis and careful anesthetic management is required.…”
Section: Discussionmentioning
confidence: 99%